2004
DOI: 10.1007/s00497-003-0199-z
|View full text |Cite
|
Sign up to set email alerts
|

AOM3 and AOM4 : two MADS box genes expressed in reproductive structures of Asparagus officinalis

Abstract: The MADS box genes participate in different steps of vegetative and reproductive plant development, including the most important phases of the reproductive process. Here we describe the isolation and characterisation of two Asparagus officinalis MADS box genes, AOM3 and AOM4. The deduced AOM3 protein shows the highest degree of similarity with ZAG3 and ZAG5 of maize, OsMADS6 of rice and AGL6 of Arabidopsis thaliana. The deduced AOM4 protein shows the highest degree of similarity with AOM1 of asparagus, the SEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…Similar results have been obtained in zag3 in situ hybridization and, moreover, zag3 mutants produce extra carpels in the ear (Thompson et al, 2009). These data are consistent with many other studies that have detected expression in carpels and ovules in angiosperms (Ma et al, 1991;Mena et al, 1995;Rounsley et al, 1995;Moon et al,1999;Tsuchimoto et al, 2000;Boss et al, 2002;Pelucchi et al, 2002;Hsu et al, 2003;Losa et al, 2004;Petersen et al, 2004;Chanderbali et al, 2006;Fan et al, 2007), except in Persea and Magnolia where RT-PCR failed to detect AGL6 expression in the carpel . Curiously, yeast two-hybrid data fail to show any interaction of AGL6-like proteins with B and C class MADS box proteins in rice (Moon et al, 1999), whereas the maize AGL6 homolog, ZAG3, does interact with the AG homolog, ZAG1 (Thompson et al, 2009).…”
Section: Agl6-like Expression Is Conserved In Carpel Development and supporting
confidence: 91%
See 4 more Smart Citations
“…Similar results have been obtained in zag3 in situ hybridization and, moreover, zag3 mutants produce extra carpels in the ear (Thompson et al, 2009). These data are consistent with many other studies that have detected expression in carpels and ovules in angiosperms (Ma et al, 1991;Mena et al, 1995;Rounsley et al, 1995;Moon et al,1999;Tsuchimoto et al, 2000;Boss et al, 2002;Pelucchi et al, 2002;Hsu et al, 2003;Losa et al, 2004;Petersen et al, 2004;Chanderbali et al, 2006;Fan et al, 2007), except in Persea and Magnolia where RT-PCR failed to detect AGL6 expression in the carpel . Curiously, yeast two-hybrid data fail to show any interaction of AGL6-like proteins with B and C class MADS box proteins in rice (Moon et al, 1999), whereas the maize AGL6 homolog, ZAG3, does interact with the AG homolog, ZAG1 (Thompson et al, 2009).…”
Section: Agl6-like Expression Is Conserved In Carpel Development and supporting
confidence: 91%
“…Expression in microsporangia was detected in gymnosperms as well as in several angiosperms but not in all (Ma et al, 1991;Mena et al, 1995;Rounsley et al, 1995;Tandre et al, 1995;Liu and Podila, 1997;Mouradov et al, 1998;Moon et al,1999;Winter et al, 1999;Tsuchimoto et al, 2000;Boss et al, 2002;Pelucchi et al, 2002;Hsu et al, 2003;Losa et al, 2004;Petersen et al, 2004;Chanderbali et al, 2006;Fan et al, 2007). Our in situ hybridizations showed that AGL6-like genes are expressed in stamens only in J. ascendens, the grass S. angustifolia in Anomochlooideae, and in Ehrhartoideae.…”
Section: Agl6-like Expression Is Conserved In Carpel Development and mentioning
confidence: 63%
See 3 more Smart Citations